Effect of prenap coffee on daytime sleepiness in university students - Upadhyay, Dishant B.; Agrawal, Siddharth B.; Verma, Anita; Mahajan, Neeraj; Shah, Nilima (International Journal of Research in Medical Sciences, 2020)
Background: Daytime sleepiness impairs academic performance in college students. Napping is a counter to daytime sleepiness, but often causes sleep inertia on waking up. Caffeine absorption from beverages peaks 30 minutes after their ingestion presenting a window of opportunity to have a short nap such that the time of waking up is in synchrony with onset of action of caffeine; thereby abolishing post-nap inertia and achieving synergistic mitigation of fatigue. Objective of this study to assess effect of nap, coffee, ‘coffee and nap’ and ‘wakeful break without coffee’ on daytime sleepiness using Psychomotor Vigilance Tests (PVTs) and Karolinska Sleepiness Scale (KSS) score. Methods: After Institutional Review Board clearance, 10 subjects (aged 19-21 years) were selected using their Epworth Sleepiness Scale score (ESS >5) and called to the study site 8 times on different days to be exposed to these four conditions twice - only coffee (standardized), only nap (30min), coffee immediately followed by 30min nap, wakeful break (30min) without coffee or nap. Pre and post scores were recorded for electronic PVT (Reaction Time and Motor Responsiveness) and KSS for each attempt. Results: Test outcome was associated with intervention used (p=0.00001). ‘Nap only’ group was associated with deterioration in outcomes (p=0.00001), accounting for highest percentage (41%) of all deteriorated test outcomes. ‘Coffee only’ group was associated with improvement in test scores (p=0.00001), responsible for highest share (38.8%) of all improved test outcomes. ‘Nap only’ and ‘Coffee-nap’ group showed improvement in 11.67% and 21.67% of outcomes respectively. Conclusions: Pre-nap coffee is a proactive counter-measure to post nap sleep inertia.